ANTIOXIDANT ACTIVITY OF TEMBESU (Fagraea fragrans Roxb.) LEAF - Budi Eko Wahyudi; Salni Salni; Arum Setiawan (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2022)
Herbal medicine is becoming a trend in curing several diseases especially degenerative because of the bad effects of synthetic drugs. Tembesu plant (Fagraea fragrans Roxb.) is traditionally used for degenerative diseases. This study aims to separate bioactive compounds (active fraction), pure isolate compounds from tembesu leaf, then observe antioxidant activity. The methods used are maceration extraction, liquid-liquid fractionation, purification of compounds by gravity chromatography column and antioxidant activity by scavenging DPPH radicals. The results showed that the active antioxidant fractions were n-hexane and ethyl acetate fractions. The results of purification of antioxidant compounds, obtained 6 isolates N1, N2, N4, N5, E8 and E11. Antioxidant activity (IC50) of pure isolates N1 (13.72 ppm), N2 (28.93 ppm), N4 (110.44 ppm), N5 (177.23 ppm), E8 (82.50 ppm) and E11 (12 ,86 ppm). The antioxidant compounds that have been isolated are terpenes (N1, N2, N4, E8), phenols (N5) and flavonoids (E11). This study concluded that tembesu leaf have antioxidant potential. Antioxidant bioactive compounds in tembesu leaf have the potential to be developed into standardized herbs and phytopharmaceuticals.